Mental Health Challenges of Refugee Children - Majerčáková Albertová, Silvia (European Integration Studies, 2024)
Worldwide, the number of refugee children and youth is staggering. It is well-documented that refugee children face various types and varying extents of mental health challenges. Providing an overview of the mental health challenges that this population faces, this chapter discusses the current mental health status of refugee children through the lens of prominent psychological theories. A psychosocial approach to human development is introduced, moving beyond the traditional approach of diagnosis and treatment of mental health symptoms, adopting a holistic ecological approach targeting both risk and resilience factors that promote sustainable mental health and well-being in refugee children. Through the motivational theory of human needs, refugee children’s needs are outlined as their basic human rights, offering a rationale for comprehensive mental health services to be provided at the individual, family, and community levels. With the overarching aim of promoting complete mental health of refugee children towards a state of well-being, a system of interventions is outlined, which considers the complex needs of these children and their families. A family is a system of its own; however, it is also a subsystem within a larger societal system. A subsystem can thrive only if, at the societal level, an open-minded, prejudice-free, and tolerant approach is adopted towards refugee children and their families. Each child is primarily a child with human rights and deserves to thrive in a psychologically healthy environment to have a chance to achieve positive life outcomes.